Multimodal Learning Material in An English-Speaking Class in Kampung Baluwarti - Fitria Yuliani (Journal of English Language Teaching and Learning (JETLE), 2022)
This study mainly concerned about the use of Multimodal learning material in enhancing students’ English-speaking skill. The study was carried out in Kampung Baluwarti Surakarta as the researcher was one of the tutors involved in Community service team of ABA St. Pignatelli Surakarta during January to March 2022. The main objective of this study was to investigate the implementation of multimodal learning material used in English speaking class of Kampung Baluwarti tourism community. Furthermore, their perceptions towards the use of the learning material were depicted as well. Qualitative research with narrative design was used in this study. The researcher collected the data through a variety of data collection got from in-depth interviews with the students, observation, and documents. It was discovered that multimodal learning material could be presented in various mode such as sound, picture, motion and written text to accommodate students’ learning. It helped students to be more active in practicing the target language. Students’ involvement was seen more during the lesson. Moreover, students seemed to be excited and comfortable during the class. In other words, multimodal learning material applied in the teaching learning process makes a difference in students’ speaking skill achievement.